(untitled) (AYUSHDHARA, 2023)
Hyperlipidaemia does not bear a precise reference in Ayurveda though the study of Ayurvedic literature bears some implicit allusions. This might be due to the fact that it is a metabolic disorder and not a full-fledged disease in itself. The term hyperlipidemia is not used in our classic. But we can correlate it with Medovaha Sroto Dushti. Hyperlipidaemia is term used to denote raised serum levels of cholesterol or triglycerides or both. Raised total cholesterol is a major cause of disease burden in both the developed and developing world as a risk factor for ischemic heart disease and stroke. CVDs accounts for one third of total deaths around the world, it is believed that CVDs will turn out to be the main cause of death and disability worldwide by the year 2020. Lack of exercise and Kaphavardhak Ahar Vihar are the two main causes of vitiation of Medovaha Srotas. Dietary low fat intake or nutrition supplementation is the key of lowering blood lipids as art for keeping hyperlipidaemia in control and manageable.